Properties and clinical application of high density glass ionomers available in Lima-Peru - Caso Guerra, Rosalyn Mariela (2021)
The objective of the review was to understand the properties and clinical application of the different high-density glass ionomers available in Lima, Perú. A review of the scientific literature about high-density glass ionomers, was conducted from January 2010 to December 2019. This review was performed in SciELO, Pubmed and Google Scholar databases. The descriptors used in the search were: glass ionomer cements, high density glass ionomers and physical properties, the combinations between them and their equivalent in English. Ultimately forty articles that met the inclusion criteria, were selected. The high-density ionomers available in Lima-Peru are Ionofil® Plus (VOCO), KetacTM Molar Easymix (3M ESPE), Fuji IX GP (GC corporation) and EQUIA Forte™® GC (Europe GC). The properties and clinical application of all these ionomers are presented. According to the literature review, of the five groups studied; EQUIA Forte presented excellent adhesion to enamel and dentin. Fuji IX GP can be placed in Class II restorations without occlusal contacts and EQUIA Forte can be used in small Class II with / without occlusal contacts, and cautiously in large MOD cavities following the manufacturer’s recommendations.